The Lyt-2 molecule recognizes residues in the class I alpha 3 domain in allogeneic cytotoxic T cell responses (The Rockefeller University Press, 1988)
The involvement of the different domains of the MHC class I molecule in CTL recognition was investigated. mAbs specific for the alpha 1/alpha 2 domains of H-2Ld interfered with both the primary and secondary generation and effector function of in vitro Ld-specific CTL. mAbs specific for the alpha 3 domain of H-2Ld interfered with the generation and function of primary in vitro Ld-specific CTL; however, there was no effect on the in vitro generation of secondary CTL and only partial inhibition of their function. In vivo treatment with graft-specific antibodies to both the alpha 3 domain and the alpha 1/alpha 2 domains together resulted in a dramatic enhancement of Ld- or Dd-disparate skin grafts, whereas the individual mAbs showed minimal effects. This suggested that the class I alpha 3 domain is recognized by alloreactive CTL. Several approaches were undertaken to examine whether recognition of the alpha 3 domain determinants is mediated by the Lyt-2 molecule. When mAbs specific for the alpha 3 domain of either H-2Ld or H-2Dd were used in vivo and in vitro, the resulting CTL population was not inhibited by antibody to the alpha 3 domain and was only partially inhibited by antibody to Lyt-2. We therefore observed a correlation between the effects of antibody to the class I alpha 3 domain of the target molecule and antibody to the Lyt-2 molecule on the CTL. To further test the relationship between CTL recognition of the alpha 3 domain and the involvement of Lyt-2, we used a cell expressing a mutation in the alpha 3 domain of the Dd molecule. The mutation resulted in a single amino acid substitution of glu to lys at residue 227 of the alpha 3 domain. Consistent with an earlier report, cells expressing the mutant Dd lys molecule were not lysed by CTL from a primary stimulation against the wild-type Dd glu molecule. However, this same cell line was killed by the Lyt-2-independent secondary Dd- specific CTL generated in the presence of antibody to the alpha 3 domain in vivo and in vitro. Furthermore, cells expressing the mutant Dd lys molecule failed to stimulate a primary response. In conclusion, several independent lines of evidence indicate that residues in the alpha 3 domain of the class I molecule are involved in recognition by the Lyt-2 molecule, and that Lyt-2-mediated recognition can be specifically blocked using mAb to determinants in the alpha 3 domain.